The complete mitochondrial genome of the Atlantic spiny lumpsucker Eumicrotremus spinosus (Fabricius, 1776). Issue 3 (4th March 2023) - Pinninti, Likith R.; Maurstad, Marius F.; Hoff, Siv N.K; Kristensen, Torstein; Noble, Leslie R.; Jentoft, Sissel; Fernandes, Jorge M. O.
Abstract: The complete mitogenome of the Atlantic spiny lumpsucker ( Eumicrotremus spinosus) was generated using the PacBio Sequel II HiFi sequencing platform. The mitogenome assembly has a length of 19, 281 bp and contains 13 protein-coding sequences, 22 tRNA genes, 2 rRNA genes, one control region containing the D-loop (2383 bp) and a duplicate control region (1133 bp) Phylogenetic analysis using maximum likelihood revealed that E. spinosus is closely related to the Siberian lumpsucker ( E. asperrimus ). The mitogenome of the spiny lumpsucker will be useful in population genomics and systematic studies of Cyclopteridae, Liparidae, and Cottidae.